An Australian study on feigned mTBI using the Inventory of Problems – 29 (IOP-29), its Memory Module (IOP-M), and the Rey Fifteen Item Test (FIT). Issue 5 (3rd September 2022) - Gegner, Jennifer; Erdodi, Laszlo A.; Giromini, Luciano; Viglione, Donald J.; Bosi, Jessica; Brusadelli, Emanuela
Abstract: We investigated the classification accuracy of the Inventory of Problems − 29 (IOP-29), its newly developed memory module (IOP-M) and the Fifteen Item Test (FIT) in an Australian community sample ( N = 275). One third of the participants ( n = 93) were asked to respond honestly, two thirds were instructed to feign mild TBI. Half of the feigners ( n = 90) were coached to avoid detection by not exaggerating, half were not ( n = 92). All measures successfully discriminated between honest responders and feigners, with large effect sizes ( d ≥ 1.96). The effect size for the IOP-29 ( d ≥ 4.90), however, was about two-to-three times larger than those produced by the IOP-M and FIT. Also noteworthy, the IOP-29 and IOP-M showed excellent sensitivity (>90% the former, > 80% the latter), in both the coached and uncoached feigning conditions, at perfect specificity. Instead, the sensitivity of the FIT was 71.7% within the uncoached simulator group and 53.3% within the coached simulator group, at a nearly perfect specificity of 98.9%. These findings suggest that the validity of the IOP-29 and IOP-M should generalize to Australian examinees and that the IOP-29 and IOP-M likely outperform the FIT in the detection of feigned mTBI.